Adsorption Isotherm and Kinetic Studies of Phenol on Meskeat Activated Carbon - Osman Ibraheem, Nabil Suliman (Gezira Journal of Engineering and Applied Sciences; Vol 14 No 2 (2019), 2019)
Adsorption is a commonly used process for the removal of pollutants from aqueous solutions utilizing many adsorbents. Phenol in water is one of the pollutants that can be removed by activated carbon. The Meskeat activated carbon sample was; crushed into fine powder (75μm), heated in an oven at temperature 110 o C and kept in a desiccator. It was analyzed for pH, pH pzc and scanned by Electron Microscopy (SEM). It has been found that pH (8.1) and pH PZC (7.13). The sample contain calcium, potassium, chlorine, sulphur, oxygen and carbon. The morphological aspects of activated carbon were rich porous particles with fibrous morphology and also of angular- shaped particles as analyzed by SEM. The equilibrium time of phenol on activated carbon was found to be 150 min for phenol solution and the adsorption capacity increased with increase in the initial phenol concentration. The experimental data at equilibrium were analyzed using two adsorption isotherms models(Langmuir and Freundlich), and the Langmuir's isotherm model is better than Freundlich isotherm, according to the high value of correlation coefficient (R 2 ). Also the results of adsorbent dose from 0.5 g/L to 3 g/L indicated that an increase in the activated carbon mass decreases the residual concentration of phenol solution. The results show that pseudo-second order kinetics model is better than first order.             تعد عملية الامتزاز من العمليات التي تستخدم لإزالة الملوثات من المحاليل المائية وذلك باستخدام عدة مواد مازة. استخدم في هذه الدراسة الكربون المنشط لإزالة الفينول من المحاليل المائية. عينة كربون المسكيت المنشط تم سحقها إلى بدرة ناعمة ثم غربلت بواسطة غربال 75μm . جففت العينة في فرن عند درجة حرارة 110 o C وحفظت في مجفف لحين الاستخدام. حللت العينة بواسطة دراسة حمضية العينة، نقطة شحنة الصفر والماسح الالكترونى الضوئي. وجد أن حمضية العينة(8.1)، نقطة شحنة الصفر((7.13. توصلت الدراسة إلى أن التركيب الكيميائي في العينة هو الكالسيوم، البوتاسيوم، الكلور، الكبريت، الاكسجين والكربون. أيضاً النتائج المتحصل عليها بواسطة الماسح الالكتروني الضوئي أوضحت بأن السمات العامة لسطح عينة كربون المسكيت المنشط هي عبارة عن جزيئات مسامية ليفية وذات زوايا. خلصت الدراسة إلى أن الزمن اللازم لحدوث الاتزان على سطح الكربون المنشط يساوى (150 دقيقة) لمحلول الفينول وسعة الامتزاز تزيد بزيادة التركيز الابتدائي لمحلول الفينول. النتائج التجريبية عند الاتزان تم تحليلها باستخدام اثنين من ايسوثيرمات الامتزاز( لانكمير وفريندلش)، توصلت الدراسة إلى أن ايسوثيرم لانكمير أفضل من ايسوثيرم فريندلش وذلك اعتماداً على القيمة العالية لمعامل الارتباط(R 2 ). بالإضافة إلى ذلك وجد أن زيادة كمية المادة المازة في المدى (0.5 - 3 g/L) يقلل من تركيز المتبقي للفينول في المحلول المائي. أظهرت النتائج أن تفاعلات الرتبة الكاذبة الثانية مفضلة أكثر من تفاعلات الرتبة الكاذبة الأولى.